Research on Hydrogen Production from Ammonia Decomposition by Pulsed Plasma Catalysis - Yuze He; Neng Zhu; Yunkai Cai (Molecules)
Driven by dual-carbon targets, marine engines are accelerating their transition towards low-carbon and zero-carbon. Ammonium–hydrogen fusion fuel is considered to be one of the most promising fuels for ship decarbonization. Using non-thermal plasma (NTP) catalytic ammonia on-line hydrogen production technology to achieve hydrogen supply is one of the most important means to guarantee the safety and effectiveness of hydrogen energy in the storage and transportation process. However, the efficiency of ammonia catalytic hydrogen production can be influenced to some extent by the presence of several factors, and the reaction mechanism is complex under the conditions of ship engine temperature emissions. This makes it difficult to realize the precise control of plasma catalytic hydrogen production from ammonia technology under temperature emission conditions, thus restricting an improvement in the ammonia conversion rate. In this study, a kinetic model of hydrogen production from ammonia catalyzed by NTP was established. The influencing factors (reaction temperature, pressure, N2/NH3 ratio in the feed gas) and mechanism path of hydrogen production from ammonia decomposition were explored. The results show that the increase in reaction temperature will lead to an increase in the ammonia conversion rate, while the ammonia conversion rate will decrease with the increase in reaction pressure and N2/NH3 ratio. When the reaction temperature is 300 K, the pressure is 1 bar, the feed gas is 98%N2/2%NH3, and the ammonia conversion rate is 16.7%. The reason why the addition of N2 is conducive to the hydrogen production from NH3 decomposition is that the reaction N2(A3) + NH3 => N2 + NH2 + H, triggered by the electron excited-state N2(A3), is the main reaction for NH3 decomposition.